2011
DOI: 10.1016/j.freeradbiomed.2011.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of Nrf2/ARE activators, CDDO ethylamide and CDDO trifluoroethylamide, in a mouse model of amyotrophic lateral sclerosis

Abstract: Oxidative damage, neuroinflammation, and mitochondrial dysfunction contribute to the pathogenesis of ALS, and these pathologic processes are tightly regulated by the Nrf2/ARE (NF-E2 related factor 2/antioxidant response element) signaling program. Therefore, modulation of the Nrf2/ARE pathway is an attractive therapeutic target for neurodegenerative diseases such as ALS. We examined two triterpenoids, CDDO (2-cyano-3, 12-dioxooleana-1,9-dien-28-oic acid) ethylamide (CDDO-EA) and CDDO-trifluoroethylamide (CDDO-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
132
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 186 publications
(135 citation statements)
references
References 57 publications
3
132
0
Order By: Relevance
“…12 To further study the involvement of Nrf2 pathway in the process of motor neuron degeneration in SOD1-G93A mice, we generated double mutant mice, Nrf2 À / À SOD1-G93A, by mating SOD1-G93A mice to Nrf2 À / À animals with the same genetic background. The Nrf2 gene knockout was confirmed by PCR examination (Figure 2a).…”
Section: Significant Upregulation Of Cytoprotective Phase II Enzymes mentioning
confidence: 99%
See 1 more Smart Citation
“…12 To further study the involvement of Nrf2 pathway in the process of motor neuron degeneration in SOD1-G93A mice, we generated double mutant mice, Nrf2 À / À SOD1-G93A, by mating SOD1-G93A mice to Nrf2 À / À animals with the same genetic background. The Nrf2 gene knockout was confirmed by PCR examination (Figure 2a).…”
Section: Significant Upregulation Of Cytoprotective Phase II Enzymes mentioning
confidence: 99%
“…10,11 In this context, several studies demonstrated that Nrf2/ARE activators provided robust neuroprotective effect and ameliorated the disease progression in SOD1-G93A transgenic mice. 12,13 Notably, upregulation of Nrf2 expression was found in the nucleus of motor neurons in lumbar anterior horn of ALS model mice. 14 We also reported that significant HO-1 induction was detected in the lumbar spinal cord of ALS mice.…”
mentioning
confidence: 98%
“…CDDO-MA also improves spatial memory and reduces the number and size of amyloid plaques in the hippocampus in a model of Alzheimer's disease in which mice carry two mutations in the human amyloid precursor protein (Dumont et al, 2009). Compared with CDDO-MA, higher drug levels of CDDO-EA and CDDO-TFEA can be obtained in the brain, and both of these amides prolong survival in transgenic mouse models of Huntington's disease (Stack et al, 2010) and ALS (Neymotin et al, 2011). Even when treatment is delayed until the onset of motor symptoms in G93A SOD1 mice, the SOs slow progression of ALS and extend the lifespan of these mice (Neymotin et al, 2011).…”
mentioning
confidence: 99%
“…Subsequent work by Sarlette and colleagues has shown that NRF2 transcription and translation is also decreased in SALS cases (Sarlette et al 2008). Most recently, it has been demonstrated that activation of Nrf2 in NSC34 SOD1-related ALS cell models, primary motor neurone and astrocyte co-cultures and in the SOD1 G93A mouse model all improve neuronal survival (Neymotin et al 2011;Vargas et al 2008a). Primary astrocyte cultures prepared from mutant SOD1 rodent models have been shown to increase motor neuronal death in co-cultures (Nagai et al 2007;Vargas et al 2006).…”
Section: Results From Use Of Cellular Models Of Alsmentioning
confidence: 99%